Target‐Directed Azide‐Alkyne Cycloaddition for Assembling HIV‐1 TAR RNA Binding Ligands. (25th May 2020) - Paul, Rakesh; Dutta, Debasish; Paul, Raj; Dash, Jyotirmayee
Abstract: The highly conserved HIV‐1 transactivation response element (TAR) binds to the trans‐activator protein Tat and facilitates viral replication in its latent state. The inhibition of Tat–TAR interactions by selectively targeting TAR RNA has been used as a strategy to develop potent antiviral agents. Therefore, HIV‐1 TAR RNA represents a paradigmatic system for therapeutic intervention. Herein, we have employed biotin‐tagged TAR RNA to assemble its own ligands from a pool of reactive azide and alkyne building blocks. To identify the binding sites and selectivity of the ligands, the in situ cycloaddition has been further performed using control nucleotide (TAR DNA and TAR RNA without bulge) templates. The hit triazole‐linked thiazole peptidomimetic products have been isolated from the biotin‐tagged target templates using streptavidin beads. The major triazole lead generated by the TAR RNA presumably binds in the bulge region, shows specificity for TAR RNA over TAR DNA, and inhibits Tat–TAR interactions. Abstract : Taking the lead : The highly dynamic secondary TAR RNA structure of HIV‐1 is used to template cycloaddition reactions leading to the generation of triazole‐containing thiazole peptidomimetics as selective leads. The triazole ligand with flexible methylene units selectively binds to TAR RNA over TAR RNA without a bulge and TAR DNA. The ligand presumably binds in the bulge region of the TAR RNA and inhibits its interaction with the Tat peptide.